Development of an IoT-Based Parking Space Management System Design - Wang, Ange; Qin, Zhengtao (International Journal for Applied Information Management, 2023)
With the improvement of people's quality of life and the rapid development of the automobile consumer market, the problem of urban parking difficulties has become increasingly prominent. In addition to the insufficiency of the number of supporting parking spaces, the backwardness of the traditional parking lot operation model has led to insufficient openness and transparency of various information, which limits the ability of drivers to obtain parking space information, and limited parking spaces cannot be adequately obtained. Utilization is also one of the reasons for the increasing difficulty of urban parking. This article aims to study the design of parking space management system based on Internet of Things technology, choose TechIO technology to realize wireless communication between parking spaces in the parking lot, analyze the advantages of TechIO technology and the needs of parking space management system, and build a simulation based on the system design the test environment has made relevant tests on the various items of the system. The test results show that the use of TechIO technology makes the system have the characteristics of strong adaptability, low cost, and low power consumption, which not only eliminates the complicated wiring costs in the parking lot, but also brings great convenience to the deployment of parking lot nodes.